2015
DOI: 10.1007/s00330-015-3949-z
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance elastography for staging liver fibrosis in non-alcoholic fatty liver disease: a diagnostic accuracy systematic review and individual participant data pooled analysis

Abstract: Objectives We conducted an individual participant data (IPD) pooled analysis on the diagnostic accuracy of magnetic resonance elastography (MRE) to detect fibrosis stage in patients with NAFLD. Methods Through a systematic literature search, we identified studies of MRE (at 60–62.5Hz) for staging fibrosis in patients with NAFLD, using liver biopsy as gold standard and contacted study authors for IPD. Through pooled analysis, we calculated the cluster-adjusted AUROC, sensitivity and specificity of MRE for any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
163
3
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(186 citation statements)
references
References 59 publications
10
163
3
10
Order By: Relevance
“…The ability of MRE to discriminate between NASH from non-NASH was modest (AUROC 0.73) [56••]. Recently, a systematic review evaluated nine studies (232 NAFLD patients) and found that the summary AUROCs for ≥ F1, ≥ F2, ≥ F3 and F4 were 0.86, 0.87, 0.90 and 0.91, respectively [57].…”
Section: Magnetic Resonance Elastography (Mre)mentioning
confidence: 99%
“…The ability of MRE to discriminate between NASH from non-NASH was modest (AUROC 0.73) [56••]. Recently, a systematic review evaluated nine studies (232 NAFLD patients) and found that the summary AUROCs for ≥ F1, ≥ F2, ≥ F3 and F4 were 0.86, 0.87, 0.90 and 0.91, respectively [57].…”
Section: Magnetic Resonance Elastography (Mre)mentioning
confidence: 99%
“…Проте ІНЦПГ, за даними зарубіжних публіка-цій, виявляють досить часто при різних імунологіч-них захворюваннях, включаючи системний черво-ний вовчак, тяжку міастенію, системний склероз, глютенову хворобу, тиреоїдит, ревматоїдний артрит, хворобу Крона, синдром Фелті, синдром Шегрена, автоімунний гепатит, первинний біліарний цироз пе-чінки, варіабельний некласифікований імунодефіцит і гіпергаммаглобулінемію, що дозволяє припустити з високою часткою ймовірності імунологічний ха-рактер етіології [9][10][11][12][13][14][15][16][17][18][19]. Однак імунологічна природа вимагає більш детального морфологічного спостере-ження та аналізу.…”
unclassified
“…Анало-гічно підвищена захворюваність на гломерулонефрит й утворення імунних комплексів зазначалися в паці-єнтів з ІНЦПГ після спленоренального шунтування порівняно з тими, у кого печінка була в нормі [17][18][19][20]. Одним з імовірних механізмів є дисбаланс кількох імуноглобулінів або цитокінів, що також може при-зводити до мікротромбозу, активувати фіброгенез.…”
unclassified
See 2 more Smart Citations